Analisis Kompetensi Wasit Bola Voli Kabupaten Wonosobo terhadap Peraturan Permainan Bola Voli Tahun 2017 - Kristianto, Okta Dwi; Nurharsono, Tri (Universitas Negeri Semarang, 2023)
Volleyball games have referee rules in running volleyball matches, usually there are still many referees who don't understand the rules of volleyball games, many games deviate from the rules that have been set, especially in Wonosobo Regency. This research is included in descriptive research using qualitative research methods through documentation studies, observations, interviews, and field notes. The results of the referee's assessment research in Wonosobo Regency based on the 2017 Volleyball Game Regulations namely in the very good category. Obstacles found in Volleyball Referees in Wonosobo Regency in the use of the 2017 Volleyball Game Rules. Based on the results of research that has been carried out on Volleyball Referees in Wonosobo Regency, it can be concluded that Volleyball Referees in Wonosobo Regency have referred to the Volleyball Game Rules of 2017 in every match but there are still some obstacles, one of which is reading interest. So it is recommended that the referee continues to increase interest in reading in order to minimize errors.